THE DISTRIBUTION OF FLOOD HYDROGRAPH RECESSION CONSTANT FOR CHARACTERIZATION OF KARST SPRING AND UNDERGROUND RIVER FLOW COMPONENTS RELEASING WITHIN GUNUNG SEWU KARST REGION - Tjahyo Nugroho Adji; M. Misqi (Faculty of Geography, Universitas Gadjah Mada, 2010)
This research is carried out within two caves with underground river andone karst spring, which is located in Gunung Sewu karst area, Gunung Kidul. Theobjective of this research is to recognize some flood hydrograph properties of karstaquifer characterization in order to compare the comportment of aquifer to releaseits flow components between underground river and karst spring. Water level dataloggers are installed within two caves and one karst spring represent upper,middle, and lower elevation of karst topography, which are Beton, Seropan, andToto Cave, respectively. In addition, time series discharge measurement incorrespond to minimum, average, and maximum flow events is conducted toformulate the Annual Stage Discharge Rating Curve. Thereby, the full year riverhydrograph may be defined. Afterwards, by selecting several flood hydrographevents, the recession constant in each cave including diffuse flow (Kb), and fissureflow (Ki), and conduit flow (Kc) recession constant, is then calculated andcompared in every location. The result shows that Beton Spring that represents theupper part of research area confirms the quickest respond towards rainfall events.Also, this point specifies the medium number of diffuse recession constant(Kb=0.983), compared to Seropan (0.996), and Toto (0.937), means that theaquifer surrounding Toto Cave release its groundwater storage faster than BetonSpring and Seropan Cave. On the contrary, Seropan Cave performs the highestvalue of diffuse recession constant (0.996) and this situation is confirmed by its dryseason discharge that still above 810 lt/second.